How to train your highlander ebook - English, Christy (Broadswords and Ballrooms, 2016)
" fast-paced...humorous and sensual"—Publishers Weekly A foolproof plan to avoid marriage: 1. Always carry at least three blades. 2. Ride circles around any man. 3. Never get caught in a handsome duke's arms. Wild Highlander Mary Elizabeth Waters is living on borrowed time. She's managed to dodge the marriage banns up to now, but even Englishmen can only be put off for so long...and there's one in particular who has her in his sights. Harold Percy, Duke of Northumberland, is enchanted by the beautiful hellion who outrides every man on his estate and dances Scottish reels while the ton looks on in horror. The more he sees Mary, the more he knows he has to have her, tradition and good sense be damned. But what's a powerful man to do when the Highland spitfire of his dreams has no desire to be tamed... Broadswords and Ballrooms: How to Seduce a Scot (Book 1) How to Wed a Warrior (Book 2) How to Train Your Highlander (Book 3) Praise for Christy English: "Grace Burrowes and Amanda Quick fans will enjoy the strong ladies in the latest fun read from the ascending English." —Booklist "With its quick and engaging characters, here's a pleasurable evening's escape." —RT Book Reviews